Freudarwin: Evolutionary Thinking as a Root of Psychoanalysis - Marcaggi, Geoffrey; Guénolé, Fabian (Frontiers in Psychology, 2018)
Abstract: This essay synthesizes the place of biological evolutionism in the early history of psychoanalysis, and shows the implicit significance of German Darwinism in Sigmund Freud’s whole psychoanalytical works. In particular, Freud, together with Sándor Ferenczi (1873-1933), applied to mental disorders hypotheses inspired by August Pauly’s (1850-1914) psychological Lamarckism and Ernst Heckel (1834-1919) theory of recapitulation. Both of these theories rested upon the principle of inheritance of acquired characteristics, and were disproved by biological discoveries during the interwar period. However, despite these scientific progresses, Freud never gave up his idea of inherited unconscious memories, and we try here to sketch out what would have cost him a renunciation to such outdated biological principles. Notwithstanding, Sigmund Freud was the first to elaborate on evolutionary causes of mental syndromes, which makes of him the forerunner of current neo-Darwinian psychopathology, with few continuators to date within the psychoanalytic field. Nowadays, the extended neo-Darwinian synthesis and affective neuroscience may pave the way for a rational Darwinian approach to human mental disorders, which would take into account the whole neurological and psychological evolution of species, and be centered on emotions and their vicissitudes.